GREEN JOBS AND ECOLOGICAL JUSTICE: THE FUTURE OF COMMUNITY-BASED FOREST MANAGEMENT THROUGH SOCIAL FORESTRY SCHEMES - Teo, Ryan; Wong, Lucas; Koh, Megan (Yayasan Adra Karima Hubbi, 2025)
Global climate imperatives necessitate a transition to a Green Economy, placing Community-Based Forest Management (CBFM) at the forefront. However, existing Social Forestry (SF) schemes frequently prioritize conservation compliance over generating resilient, high-quality livelihoods, leading to persistent community precarity and equity concerns despite high participation rates. This study aims to systematically analyze the quality and stability of green jobs created within SF schemes and, critically, to develop a Green Jobs-Ecological Justice (GJEJ) Framework that links labor outcomes with the ethical tenets of Recognition, Participation, and equitable Distribution. A sequential explanatory mixed-methods design (QUAN to QUAL) was employed. The quantitative phase utilized a structured survey (N=450) to map job stability and demographic disparities. This was followed by qualitative case studies at four purposively selected sites (n=80 key informants) to investigate the institutional mechanisms of ecological justice. Findings revealed a 78% participation rate but a low overall Income Stability Index (45.9), concentrated in low-skill, seasonal labor. Inferential analysis demonstrated that the institutional Recognition of Local Ecological Knowledge significantly correlates with reduced income disparity (? = -0.38), whereas deficient Participation mechanisms reinforce existing demographic inequalities, particularly affecting women and youth. The study concludes that SF success is not determined by job volume but by the institutionalization of justice. The GJEJ Framework is proposed as the necessary policy tool to ensure the future of forest management is truly sustainable, resilient, and equitable.